Padrões biogeográficos e efeito das mudanças climáticas sobre as aves do Pantanal : estudo de uma espécie insetívora endêmica e um grupo de espécies frugívoras - Zucchetto, Mayara Fioreze (2021)
In recent centuries, global biodiversity has suffered from the loss of species, decline in abundance and populations. Considering this scenario, studies indicate that tropical forests are among the most threatened. In these regions, changing forest landscapes and future climate change seem to be the main drivers of biodiversity loss. Therefore, studies that propose an understanding of the effects of landscape modification and future climate change on biodiversity become a priority. In this thesis, composed of two chapters, our general objective is to identify the effects of climate change on the distribution of birds in the Pantanal. More precisely, about an endemic insectivorous species (Cercomacra melanaria) and a group of frugivorous species from this region. Current and future distribution in different climate scenarios were predicted using Ecological Niche Modeling. Our findings suggest that future changes will negatively affect (contraction of the distribution area) the C. melanaria distribution and the wealth distribution of frugivorous birds. The most climatically suitable areas in the future for the species studied here were the regions of higher altitude, mainly in the plateau that surrounds the Pantanal. However, the redistribution of these species to these higher elevation regions depends on several factors, such as: dispersal capacity of these birds, the existence of biological corridors for dispersal and how the interaction will be with the other species that inhabit there. Therefore, we can conclude that the Pantanal bird species, especially those that inhabit the Pantanal plain, will be negatively affected by the effects of climate change. The higher altitude areas, such as the plateau that surrounds the Pantanal, are extremely important, as they will be the closest climatic refuges both for an insectivorous species, endemic and with restricted distribution, as well as for the richness of frugivorous species. These areas should be considered as priorities for conservation strategies, as they have already suffered from anthropic actions due to deforestation, forest fires and the construction of Small Hydroelectric Power Plants.